Electronic Word-of-Mouth and Intention to Purchase Skincare Products and Cosmetics - Pongpeng, Preecha; Jermsittiparsert, Kittisak; Pongpeng, Teerapong; Promyoo, Taweep (International Journal of Psychosocial Rehabilitation, 2020)
Human behavior is considered to be influenced by Electronic Word-of-Mouth (e-WOM), the important information source (Filieri, 2015). The aim of this study to analyze the impact of electronic word-of-mouth that is through social media on the purchase intention of young consumers regarding cosmetics and skin care products in Indonesia. A research framework was developed with the help of literature review and tested by regression analysis with the help of SPSS on 173 young social media and skincare product users. A significant association was found to exist between the e-WOM and intention to purchase the skincare products in young Indonesian social media users influenced by credibility of information.